HUMAN RESOURCES MANAGEMENT DEVELOPMENT IN MICRO AND SMALL ENTERPRISES - Theranda Beqiri; Brikend Aziri (Human Research in Rehabilitation, 2021)
The HRM development takes on particular importance as it is considered to be an organizational function that promotes and creates space for creativity, innovation, speed, efficiency and effectiveness, thus transforming the workforce into a precious asset to the organization. In this research we investigate to what extent parts of modern HRM policies are mostly implemented in Micro and Small enterprises in Kosovo and how do they impact efficiency of the businesses and their workers, we have developed and implemented some questionnaires related to the important variables of this issue. Businesses should be able to provide competitive advantages in the market, successfully cope with the rapid advancement of technology, the effects of globalization, and the need to have an effective and efficient workforce to better fulfil their economic objectives. The HRM has its role in lifelong learning and development of employees, employee relations with co-workers and management, human relations, as well as motivation of employees. The development of HR practices has an impact not only on the economic development of an organization but also on the creation of positive effects on a country’s economic and social development. This paper has basically descriptive and analytical research. The overall conclusion of the paper is that the efficient management of human resources has an impact on the development of the private business sector, and is positively related with increases in the efficiency of the employees and the firm, therefore the need for human resources management in private businesses is necessary and essential.